THE DIFFERENCES OF SALIVARY VOLUME, pH AND ORAL CONDITIONS BETWEEN MENOPAUSAL AND NON-MENOPAUSAL WOMEN - Rosita Aisyah; Sri Tjahajawati; Anggun Rafisa (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: Menopause is the permanent cessation of menstrual cycles due to the loss of ovarian activity. This phase is characterized by physiological changes, mostly influenced by the decrease of estrogen and progesterone, as well as by the aging of tissues. These changes can involve oral cavity. Postmenopausal women are prone to changes in the oral cavity such as volume, salivary pH and oral conditions such as ulceration, bleeding gums, dry mouth and caries due to hormonal changes. Purpose: This study aimed to determine the differences in volume, salivary pH and oral conditions in menopausal women and non-menopausal women. Method: This study was using an analytic comparative method. The data obtained was secondary data from the results of the Unpad Lecturer Competency Research (RKDU) by taking a convenience sampling of 27 menopausal women and using simple random sampling of 27 non-menopausal women. The volume and salivary pH were analyzed using the non-parametric Mann-Whitney test and the data on the condition of the oral cavity were analyzed using the z-parametric test with a significance level of p<0.05. Results: The results showed that there were significant differences in salivary volume (p=0.0016), salivary pH (p=0.0191) and caries (p=0.0142), and there was no significant differences in ulceration conditions (p=0.5), bleeding gums (p=0.0806) and dry mouth (p= 0.2756) in menopausal women and non-menopausal women. Conclusion: There are differences in salivary volume, salivary pH and caries conditions, but there are no differences in ulceration, bleeding gums and dry mouth conditions in menopausal women and non-menopausal women.  Keywords: Menopausal women, Oral changes, Saliva pH, Saliva volume